A secondary Research on Medicinal Plants Mentioned in the Holy Qur’an - Md. Sanower Hossain; Zannat Urbi; Fatematuz Zuhura Evamoni; Fatama Tous Zohora; K. M. Hafizur Rahman (Journal of Medicinal Plants, 2016)
Background: Finding scientific data from the Holy Qur’an is an old trend, which emerge newly with rise of modern science. In the literature, we have found that total number of medicinal plants cited in the Holy Qur’an varies author to author.